Nickel Oxide Nano-Particles on 3D Nickel Foam Substrate as a Non-Enzymatic Glucose Sensor. Issue 15 (1st January 2019) - Hayat, Asif; Mane, Sunil Kumar Baburao; Shaishta, Naghma; Khan, Javid; Hayat, Ashiq; Keyum, Guzalnur; Uddin, Ikram; Raziq, Fazal; Khan, Muhammad; Manjunatha, G.
Abstract : One of the important factors to recover the quality of lifespan of diabetic patients is continuous intensive care of glucose to deliver information for more precise diagnosis and treatment. Up-to-date an incessant glucose sensor uses enzymes with a one-to-two-week lifespan, which forces episodic replacement. In this context, metal oxide sensor is considered as a substitute to enzymatic sensors owing to the longer lifetime. The present research demonstrate a simplistic conglomeration of nickel hydroxide (Ni(OH)2 ) and nickel oxide (NiO) nano-particles via a microwave radiation method followed by deposition on a highly porous 3D nickel foam substrate dissipating nickel nitrate Ni(NO3 )2 as the nickel source with sodium hydroxide (NaOH) as the starting material. The resultant polycrystalline NiO films were annealed and characterized by various techniques. Electrochemical studies reveal that the NiO manifested magnificent stability and outstanding catalytic activity for electrocatalytic oxidation of glucose in the aqueous solution of sodium sulfate (Na2 SO4 ), enabling an enzyme-free amperometric sensors for glucose designation. The nanorod arrays on distinctive 3D substrate are anticipating to accelerate the sensitivity and efficiency of NiO based electrochemical sensors and heterogeneous catalysts. The NiO based glucose biosensor offered improved properties having extensive linear reciprocation window for glucose concentrations, concise retaliation time, lower recognition level, prominent sensitivity as well as good stability and recyclability.